Foliar Application of Spermidine Reduced the Negative Effects of Salt Stress on Oat Seedlings - Hai, Xia; Mi, Junzhen; Zhao, Baoping; Zhang, Biru; Zhao, Zhou; Liu, Jinghui (Frontiers in Plant Science, 2022)
The effects of foliar application of spermidine (Spd) on physiological aspects of salt-stressed oat seedlings were studied. At the seeding stage the salt-sensitive variety Caoyou1 and the salt-tolerant variety Baiyan2 were treated with 70 mmol/L and 100 mmol/L of salt, followed by foliar application of 0.75 mmol/L Spd. The results showed that Spd application increased the activities of superoxide dismutase (SOD), peroxidase (POD), catalase (CAT), and ascorbate peroxidase (APX), modulated the level of endogenous hormones and the content of endogenous polyamines, and reduced the rate of O2•– production and the accumulation of H2O2 and malondialdehyde (MDA) in the seedling leaves. Application of Spd also increased the contents of soluble sugar, soluble protein and free proline and helped maintaining the osmotic balance of oat leaves. At the same time, foliar Spd treatment also helped maintaining ion nutrition balance, i.e., reduced the content of Na+ and increased the content of K+ and Ca2+ and Mg2+, and thereby stabilized the ratio of Na+/K+, Na+/Ca2+, and Na+/Mg2+. And the effect of Spd application was more obvious in Caoyou1 under the 70 mmol/L salt treatment.